PLC-β1 and cell differentiation: An insight into myogenesis and osteogenesis. (January 2017) - Ramazzotti, Giulia; Faenza, Irene; Fiume, Roberta; Billi, Anna Maria; Manzoli, Lucia; Mongiorgi, Sara; Ratti, Stefano; McCubrey, James A.; Suh, Pann-Ghill; Cocco, Lucio; Follo, Matilde Y.
Abstract: Phosphoinositide-phospholipase C-β1 (PLC-β1) plays a crucial role in the initiation of the genetic program responsible for muscle differentiation and osteogenesis. During myogenic differentiation of murine C2C12 myoblasts, PLC-β1 signaling pathway involves the Inositol Polyphosphate Multikinase (IPMK) and β-catenin as downstream effectors. By means of c-jun binding to cyclin D3 promoter, the activation of PLC-β1 pathway determines cyclin D3 accumulation. However, osteogenesis requires PLC-β1 expression and up-regulation but it does not affect cyclin D3 levels, suggesting that the two processes require the activation of different mediators.